MODELLING OF SHOCKWAVE IN CONVERGING-DIVERGING NOZZLE USING SHOCK CAPTURING METHOD - ROSLI, MOHD NAZARUDIN (Universiti Teknologi PETRONAS, 2010)
The fonnation of shock has always seen as undesirable occurrence. The knowledge about its fonnation is critical especially during design stage. Highly accurate numerical model are needed in order to accurately simulate fonnation of shock. One case study on supersonic flow separation has been selected as basis. Grid independent study is done to study the effect of grid density as well as refinement direction (axial, radial, and both axial and radial) to the accuracy of the solution. It is also desirable to investigate the fonnation of shocks under different nozzle operating pressures. The simulation is using several nozzle pressure ratios (NPRs) as manipulated parameters. Simulation results show that refinement in radial direction gives the optimum trend followiog data while refmement in both axial and radial gives quite accurate data but not followiog the experimental data trend. Higher density mesh is found to be capable of capturing weak shocks and shock-boundary layer interaction. Lastly, under different operating pressure, it is found that shocks location is closer to the throat as the nozzle pressure ratio is decreased.